2014
DOI: 10.1002/cncr.28614
|View full text |Cite
|
Sign up to set email alerts
|

Quality of end‐of‐life care in patients with hematologic malignancies: A retrospective cohort study

Abstract: Background Limited data is available on the quality of end-of-life care for patients with hematologic malignancies. In this retrospective cohort study, we compared the quality of end-of-life care between patients with hematologic malignancies and those with solid tumors. Methods All adult patients who died of advanced cancer between 9/1/2009 and 2/28/2010 while under the care of our institution were included. We collected baseline demographics and end-of-life care indicators, including emergency room visits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
261
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 268 publications
(295 citation statements)
references
References 29 publications
27
261
4
3
Order By: Relevance
“…For example, lack of access for rural residents to community-based services after clinical hours likely increases reliance on hospital care. That finding is supported by numerous studies [13][14][15] . Further work is needed to better understand the landscape of end-of-life care in Canada:…”
Section: Resultssupporting
confidence: 78%
“…For example, lack of access for rural residents to community-based services after clinical hours likely increases reliance on hospital care. That finding is supported by numerous studies [13][14][15] . Further work is needed to better understand the landscape of end-of-life care in Canada:…”
Section: Resultssupporting
confidence: 78%
“…We found that hematologic oncology specialists expressed lower comfort levels compared with their solid tumor counterparts.This is consistent with multiple studies demonstrating that hematologic oncologists were generally less comfortable with EOL care [13,14] and that patients with advanced hematologic malignancies often have lower access to acute palliative are and hospice care and more intensive EOL care [12,20]. This difference might be related to challenges in prognostication, difficulty in identifying the EOL period, the plethora of novel treatment options with curative potential, and patient preferences [13].…”
Section: Discussionsupporting
confidence: 81%
“…The three cancer subgroups were metastatic germ cell tumors and prostate cancer; metastatic lung, liver, and pancreatic cancer; and all other metastatic cancers. Patients with hematologic malignancies were excluded because it was previously reported that these patients tended to receive more aggressive EOL care [21].…”
Section: Databasementioning
confidence: 99%